Brachyuran soft-bottom assemblage from marine shallow waters in the southeastern Brazilian littoral. - Bertini, Giovana [UNESP]; Fransozo, Adilson [UNESP]; Negreiros-Fransozo, Maria Lucia (My University, 2010)
The present investigation examined the assemblages of brachyuran crabs in three bays of southeastern So Paulo State, analyzing the numbers of species and individuals, biomass, and diversity. The crabs were collected monthly in Ubatumirim, Ubatuba, and Mar Virado bays in the Ubatuba region over 2 years (1998 and 1999). In each bay, six tows were made from a fishing boat. A total of 39,820 specimens, representing 11 super families, 39 genera, and 65 species of brachyurans, were obtained. The mean number of specimens and biomass varied seasonally, which can be mainly related with the population tendencies of two dominant species in the area (Callinectes ornatus and Hepatus pudibundus). The highest numbers of individuals and species were found in Ubatuba Bay, followed by Ubatumirim and Mar Virado. The highest diversity index was estimated for Ubatumirim (H' = 2.44), followed by Ubatuba (H' = 2.37) and Mar Virado (H' = 1.86). In general, the coastal region supported high abundance and species richness concerning brachyurans, with high diversity indices, probably because of its more-heterogeneous substrate, which may afford more refuges for certain species. These results suggested that environmental conditions in this area, although they showed certain differences, are favorable for the establishment and development of a diverse brachyuran guild.